Upaya Guru Pendidikan Agama Islam dalam Mengatasi Kesulitan Baca Tulis Al-Quran Siswa di SMA Muhammadiyah 18 Sunggal - Muhammad Musa Tarigan; Mardianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The problem of reading and writing the Qur'an is not a common thing for students at school, because this problem is the hardest task for Islamic Religious Education (PAI) teachers. The purpose of this study was to determine the efforts made by Islamic Religious Education (PAI) teachers in overcoming the difficulties of reading and writing the Qur'an in students of SMA Muhammadiyah 18 Sunggal. The research method used is qualitative descriptive with primary data sources obtained from the field or research location, namely the results of interviews or observations in the field, Islamic Religious Education teachers, principals and students of SMA Muhammadiyah 18 Sunggal. The results of the study showed that the efforts of Islamic Religious Education teachers in overcoming the difficulties of reading and writing the Qur'an in students were by implementing group learning methods, lecture methods, question and answer methods, and methods of practicing writing verses of the Qur'an. The efforts made gave positive results because all students who graduated from SMA Muhammadiyah were able to read and write the Qur'an. This study is expected to be one of the guidelines for Islamic Religious Education teachers so that they can create the best solution in overcoming the difficulties of reading and writing the Qur'an in students.